Effect of real working environment/formation of oxide phase on thermoelectric properties of flexible Sb2Te3 films - Somdock, Nuttakrit; Harnwunggmoung, Adul; Sakulkalavek, Aparporn; Sakdanuphab, Rachsak (My University, 2019)
Flexible Sb2Te3 thin films, for thermoelectric generator applications, were deposited by DC magnetron sputtering. As-deposited films were annealed in air to simulated a realistic operating environment. The oxidation behavior of the films was studied by monitoring their phase change on exposure to air at different temperatures between 50 and 300 °C for annealing times from 1 to 15 h. Oxidation of Sb and Te formed Sb2Te4 and TeO2 phases when annealing above 100 °C and Sb2Te3 decomposed into oxide phases at an annealing temperature of 250 °C for 15 h. The thermoelectric performance decreased as the content of Sb2O4 and TeO2 phases increased. These findings show the limitations of Sb2Te3 films operating in air without vacuum or a protective environment. We propose that the kinetic growth of oxide formation on the Sb2Te3 thin films depend on chemical activation energy and oxygen diffusion through the oxide barrier by the variation of annealing temperature and annealing time, respectively.
Keywords: Air annealing; Flexible film; Oxide formation; Sb2Te3 film; Thermoelectric